(5m+8n)(5m+8n)=

Simple and best practice solution for (5m+8n)(5m+8n)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5m+8n)(5m+8n)= equation:


Simplifying
(5m + 8n)(5m + 8n) = 0

Multiply (5m + 8n) * (5m + 8n)
(5m * (5m + 8n) + 8n * (5m + 8n)) = 0
((5m * 5m + 8n * 5m) + 8n * (5m + 8n)) = 0

Reorder the terms:
((40mn + 25m2) + 8n * (5m + 8n)) = 0
((40mn + 25m2) + 8n * (5m + 8n)) = 0
(40mn + 25m2 + (5m * 8n + 8n * 8n)) = 0
(40mn + 25m2 + (40mn + 64n2)) = 0

Reorder the terms:
(40mn + 40mn + 25m2 + 64n2) = 0

Combine like terms: 40mn + 40mn = 80mn
(80mn + 25m2 + 64n2) = 0

Solving
80mn + 25m2 + 64n2 = 0

Solving for variable 'm'.

Factor a trinomial.
(5m + 8n)(5m + 8n) = 0

Subproblem 1

Set the factor '(5m + 8n)' equal to zero and attempt to solve: Simplifying 5m + 8n = 0 Solving 5m + 8n = 0 Move all terms containing m to the left, all other terms to the right. Add '-8n' to each side of the equation. 5m + 8n + -8n = 0 + -8n Combine like terms: 8n + -8n = 0 5m + 0 = 0 + -8n 5m = 0 + -8n Remove the zero: 5m = -8n Divide each side by '5'. m = -1.6n Simplifying m = -1.6n

Subproblem 2

Set the factor '(5m + 8n)' equal to zero and attempt to solve: Simplifying 5m + 8n = 0 Solving 5m + 8n = 0 Move all terms containing m to the left, all other terms to the right. Add '-8n' to each side of the equation. 5m + 8n + -8n = 0 + -8n Combine like terms: 8n + -8n = 0 5m + 0 = 0 + -8n 5m = 0 + -8n Remove the zero: 5m = -8n Divide each side by '5'. m = -1.6n Simplifying m = -1.6n

Solution

m = {-1.6n, -1.6n}

See similar equations:

| 2.4v+17-1.9= | | -2y=8x-4 | | -3(5u-1)+8u=9+2(4u-6) | | cos71=x/114 | | 150x-5.25=250 | | .67y+27+.75y=-24 | | 4x+16x+24= | | 660b+180=120b^3 | | (-6t+7)-4(t-3)= | | 3(7)-3y=-9 | | 150x+5.25=250 | | 48=9x-6 | | 150x+5.25=350 | | t^2+3t-8=2t-8 | | (y)dx+(2x+4y^2)dy=0 | | 5x-8(-6)=3 | | 13n-6=6n+1 | | 6x-5=29-4x | | 2x=(3553/6) | | n^3-3n^2-n=3 | | Z+9=1 | | 3-8x+28=5x+1 | | x^2+3=2x^2-3x-7 | | 3+3t-2=4t+9-2t | | b^-8/b^30 | | (x+1)(3x-4)=0 | | 4(v-1)-2=-3(-8v+8)-6v | | 6/8x2/3 | | n+5-5n+10= | | B^2+4b-70=-4 | | 4n^3=172 | | x^2-24-23x= |

Equations solver categories